Special Difficulties in Forecasting GDP in the Pandemic Situation (2020–2021): Is there a Keynesian resurgence? - Magas, Antal István (Public Finance Quarterly, 2023)
Why was it extremely difficult to forecast GDP worldwide, especially in the years of 2020-2021? Mainly because a double shock hit both the aggregate demand and supply sides, and it had substantially changed the known behaviour of key participants. Reactions of households and firms became largely unpredictable. The IMF projections of April 2020 had to be revised sharply. It appears the world economy could recover from the biggest output drop since World War II only with the help of extensive public spending schemes. We ask if one can speak of a new wave of Keynesian policies. How long this present overwhelmingly loose fiscal and monetary stance can last? One cannot tell. There are visible threats, for instance in the inflationary environment.